Challenging the Orthodoxy of Mandibular Reconstructions Comparing Functional Outcomes in Osseous versus Soft Tissue Reconstructions of the Posterolateral Mandible - Dimovska, Eleonora Olivera Felicty; Clibbon, Jonothan; Heaton, Martin; Viswanathan, Narayanan; Ridha, Hyder; James, Richard (Journal of Reconstructive Microsurgery, 2020)
Background Appropriate reconstruction of the posterolateral mandible remains controversial. Both osseous and soft tissues are vital components for an overall successful outcome and are often combined in complex defects. Their respective effect on oromandibular function in the reconstruction of different degrees of mandibular defects has been less evaluated. This study aimed to compare patient-perceived oromandibular function in osseous and soft tissue-only reconstructions following posterolateral mandibular defects, defined as limited or extended.Patients and Methods A 10-year retrospective review of consecutive patients undergoing mandibular reconstructions of the posterolateral mandible were identified. Limited defects were defined as reaching from the ipsilateral parasymphysis to anterior of the coronoid (sparing insertion of muscles of mastication). Extended defects were defined as reaching from the ipsilateral parasymphysis to posterior of the coronoid (sacrificing the muscle insertions). Functional outcomes were assessed using the University of Washington Quality of Life questionnaire, version 4.Results A total of 163 patients were identified, of which 41 patients had the particular posterolateral mandibular resections sought after. In 23 limited resections, there was no difference in functional outcome between osseous and soft tissue-only reconstructions. In 18 patients undergoing extended resections, osseous reconstructions demonstrated significantly better outcomes (p = 0.011). There were no significant differences in patient demographics between the groups.Conclusion Our study highlights the interest of soft tissue-only reconstructions of the posterolateral mandible. Limited resections seem not to benefit from complex osseous reconstruction for adequate function. Conversely, there is a noteworthy positive impact on functional outcomes in extended posterolateral mandibulectomies reconstructed with osseous tissue, compared with soft tissue only. Although a larger study is needed to identify a stronger relationship, these preliminary results could aid reconstructive decisions, particularly when considering patient morbidity.
Keywords: mandible; reconstruction; chewing